A Vinyl‐Cation‐Induced 1, 3‐Aryl Shift. Issue 50 (10th May 2017) - Fu, Liang; Damsen, Helena; Niggemann, Meike
Abstract: A net insertion of an unactivated, internal alkyne into a sp 2 –sp 3 C−C bond of simple benzylic alcohols was achieved using the rearrangement of a highly reactive vinyl cation intermediate to a stabilized allyl cation as the driving force for an unusual 1, 3‐carbon shift reaction. In the presence of 10 mol % of Al(OTf)3 as a simple, inexpensive, and abundant catalyst, high selectivity for the rearrangement was achieved. The reaction scope proved general with regard to both the alkyne and the benzylic alcohol and a range of 1, 2‐dihydroquinolines as well as 2 H ‐chromenes were obtained. Abstract : Hop scotch : The rearrangement of a vinyl cation to a stabilized allyl cation was used as the driving force for a highly unusual 1, 3‐aryl shift reaction. Thereby a net insertion of an unactivated, internal alkyne into a sp 2 –sp 3 C−C bond of benzylic alcohols was achieved in the presence of 10 mol % of Al(OTf)3 as a simple, inexpensive, and abundant catalyst. The reaction scope proved general and a range of 1, 2‐dihydroquinolines as well as 2 H ‐chromenes were obtained.